Synthesis and properties of core-shell structure of triangular Ag@Au - Satkunarajah Pratheepan. (2011)
Nanotechnology has received attention recently due to its ability to offer different material properties from the same material in the bulk phase. Gold and silver have, in particular, generated much interest due to the unique optical properties. Bimetallic nanoparticles offer a greater range of properties. Bimetallic structures, when combined with anisotropy in structures, can give rise to core shell nano particles. As geometric dimensions play an important role in the properties of such particles, a variety of properties can be obtained by varying the size and shape of the particle.